(untitled) (Communications in Computational Physics, 2018)
This paper designs a segmentation method for an image based on its Fourier spectral data. An edge map is generated directly from the Fourier coefficients without first reconstructing the image in pixelated form. Consequently the internal boundaries of the edge map are not blurred by any (filtered) Fourier reconstruction. The edge map is then processed with an edge linking segmentation algorithm. We include examples from magnetic resonance imaging (MRI). Our results illustrate some potential benefits of using high order methods in imaging.